Tom Horn [videorecording (DVD)] - McQueen, Steve, 1930-1980; Evans, Linda, 1942-; Horn, Tom, 1860-1903 (Essential Steve McQueen collection., 2005)
When he rode into Wyoming in 1900, Tom Horn was already a legend. He was as successful at wiping out rustlers as he had been at everything else he'd tried. But the West was changing, and a free spirit like Horn was a liability to the men who had hired him. Based on the true story, Tom Horn presents a harsher, less romantic vision of the West, but one that remains true to the frontier's raging spirit.